Newly diagnosed metastatic pulmonary calcification in a kidney transplantation recipient: a case report - Sojung Youn; Chul Woo Yang; Byung Ha Chung; Eun Jeong Ko (Korean Journal of Transplantation, 2022)
Metastatic pulmonary calcification (MPC) is defined as calcium deposition in lung tissues. It is commonly seen in end-stage renal disease patients. However, MPC occurring in kidney transplant recipients (KTRs) is rare. We report a case of MPC in a 55-year-old female patient after successful kidney transplantation (KT). One year after KT, bisphosphonate and vitamin D were prescribed for osteoporosis. Then, 4.5 years after KT, we incidentally found multiple nodular lesions on chest X-ray (CXR) without any symptoms. Chest computed tomography showed multiple high-density nodules. A bone scan confirmed MPC in the right middle lobe and right lower lobe. A retrospective review of pretransplant blood chemistry revealed the following: serum calcium level, 11.2 mg/dL; phosphorus level, 3.2 mg/dL; intact parathyroid hormone level, lower than 2.5 pg/mL; and 24-hour urine calcium level, within normal limits (WNL). After KT, all of these parameters remained WNL. Therefore, hidden adynamic bone disease might have been aggravated by bisphosphonate and vitamin D supplementation, causing MPC. Both were discontinued. She was monitored by routine CXR, and MPC did not progress. Since MPC is commonly asymptomatic and difficult to diagnose in KTRs, caution is required when administering such medications. Patient should be followed up with routine CXR.